Pengaruh kepuasan kerja terhadap kinerja dengan komitmen organisasi sebgai variabel intervening (studi pada mitra bangunan Kota Jambi) - Putra, Anjas Kesuma (Jurnal Dinamika Manajemen, 2023)
This research was conducted to describe and explore in depth about the variable descriptions of job satisfaction, organizational commitment and employee performance in the Jambi city supermarket building partners as well as the influence caused by job satisfaction on organizational commitment, the effect of job satisfaction on employee performance, the influence of organizational commitment on employee performance, and the effect of job satisfaction on employee performance with organizational commitment as an intervening variable. The number of samples in the study were 127 employees of Jambi city supermarket building partners. This research method is a quantitative research. The findings in this study indicate that the variable descriptions of job satisfaction, organizational commitment and employee performance at Mitra Bangunan Supermarket Jambi are categorized as high. high prediket rate. As for the influence between variables, it shows that job decision variables have a positive and significant effect on performance, while for the mediating variables that indirectly affect job satisfaction on performance, it is significant, so it can be concluded that organizational commitment has an indirect effect on job satisfaction on employee performance.